Customer's acceptance, usage and M-satisfaction of Mobile HotelReservation Apps (MHRA) / Mohd Noor Ismawi Ismail...[et al.] - Ismail, Mohd Noor Ismawi; Hemdi, Mohamad Abdullah; Sumarjan, Norzuwana; Hanafiah, Mohd Hafiz; Zulkifly, Muhammad Izzat (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
This conceptual paper aims to explore the relationship between customer acceptance and the usage of Mobile Hotel Reservation Apps (MHRA) on Mobile satisfaction (M-satisfaction). The MHRA booking is the latest booking channel offered by the hoteliers in favor of mobility and service failures exposed by the traditional method of room booking. Nonetheless, the actual usage and the success of this app have not been explored yet. The Unified Theory of Acceptance and Use of Technology (UTAUT2) was adopted as the underpinning theory of this study. The UTAUT2 framework was modified by incorporating Msatisfaction as the dependent variable. Seven propositions were suggested based on the literature review.